Application of four pricing models for orphan medicines: a case study for lumasiran - Noa Rosenberg; Evert Manders; Sibren van den Berg; Lisa J. Deesker; Sander F. Garrelfs; Saco J. de Visser; Jaap W. Groothoff; Carla E. M. Hollak (Orphanet Journal of Rare Diseases)
Abstract Background The combination of high prices and uncertain effectiveness is a growing challenge in the field of orphan medicines, hampering health technology assessments. Hence, new methods for establishing price benchmarks might be necessary to support reimbursement negotiations. In this study, we applied several pricing models containing cost-based elements to the case of lumasiran for treating primary hyperoxaluria type 1. Methods Price ranges were calculated by estimating minimum and maximum scenarios for four pricing models: Novel Cancer Pricing Model (NCP-model), AIM Model for Innovative Medicines (AIM-model), Discounted Cash Flow model (DCF-model), and the Real-Option Rate Of Return model (ROROR-model). Data was gathered from disease registries, scientific literature, Security and Exchange Committee filings, and expert opinion. A sensitivity analysis was performed to assess the parameters with the largest influence. Results Outcomes resulting from the NCP-model ranged between €87,000 and €224,000 per patient per year, between €33,000 and €340,000 for the AIM-model, between €182,000 and €748,000 for the DCF-model, and between €81,000 and €273,000 for the ROROR-model. Conclusion Outcomes of the four pricing models show wide and heterogeneous price ranges. The DCF-model might be most compatible with the case of lumasiran, due to inclusion of parameters for prevalence, incidence, prescription restrictions and cost of capital. The minimum DCF price could serve as a starting point for pricing and reimbursement negotiations. Uncertainties can be solved by more transparency on input variables.